Noninvasive and Highly Multiplexed Five-Color Tumor Imaging of Multicore Near-Infrared Resonant Surface-Enhanced Raman Nanoparticles In Vivo - Yu, Jung Ho; Steinberg, Idan; Davis, Ryan M; Malkovskiy, Andrey V; Zlitni, Aimen; Radzyminski, Rochelle Karina; Jung, Kyung Oh; Chung, Daniel Tan; Curet, Luis Dan; D’Souza, Aloma L; Chang, Edwin; Rosenberg, Jarrett; et al. (ACS nano, 2021)
In vivo multiplexed imaging aims for noninvasive monitoring of tumors with multiple channels without excision of the tissue. While most of the preclinical imaging has provided a number of multiplexing channels up to three, Raman imaging with surface-enhanced Raman scattering (SERS) nanoparticles was suggested to offer higher multiplexing capability originating from their narrow spectral width. However, in vivo multiplexed SERS imaging is still in its infancy for multichannel visualization of tumors, which require both sufficient multiplicity and high sensitivity concurrently. Here we create multispectral palettes of gold multicore-near-infrared (NIR) resonant Raman dyes-silica shell SERS (NIR-SERRS) nanoparticle oligomers and demonstrate noninvasive and five-plex SERS imaging of the nanoparticle accumulation in tumors of living mice. We perform the five-plex ratiometric imaging of tumors by varying the administered ratio of the nanoparticles, which simulates the detection of multiple biomarkers with different expression levels in the tumor environment. Furthermore, since this method does not require the excision of tumor tissues at the imaging condition, we perform noninvasive and longitudinal imaging of the five-color nanoparticles in the tumors, which is not feasible with current ex vivo multiplexed tissue analysis platforms. Our work surpasses the multiplicity limit of previous preclinical tumor imaging methods while keeping enough sensitivity for tumor-targeted in vivo imaging and could enable the noninvasive assessment of multiple biological targets within the tumor microenvironment in living subjects.